Liquid Formulation of AbobotulinumtoxinA: A 6-Month, Phase 3, Double-Blind, Randomized, Placebo-Controlled Study of a Single Treatment, Ready-to-Use Toxin for Moderate-to-Severe Glabellar Lines. (20th March 2019) - Ascher, Benjamin; Rzany, Berthold; Kestemont, Philippe; Hilton, Said; Heckmann, Marc; Bodokh, Isaac; Noah, Ernst Magnus; Boineau, Dominique; Kerscher, Martina; Volteau, Magali; Le Berre, Philippe; Picaut, Philippe
Abstract: Background: Safety and efficacy of botulinum toxin A for glabellar line (GL) treatment are well established. Currently approved formulations require reconstitution before injection. Objectives: The authors sought to assess 6-month efficacy, safety, and patient satisfaction of new ready-to-use abobotulinumtoxinA solution for injection (ASI) in patients with moderate-to-severe GL at maximum frown. Methods: The authors conducted a phase 3, double-blind, randomized, placebo-controlled trial (NCT02353871). Patients (N = 185) were randomized (2:1) to receive ASI 50 U or placebo. GL severity was evaluated at days 8, 15, 29, 57, 85, 113, 148, and 183 employing a 4-point scale for investigator's live assessment (ILA) and subject's self-assessment (SSA). Primary endpoint was ILA of GL at maximum frown at day 29, and secondary endpoints were ILA and SSA of GL at maximum frown (all time points), patient satisfaction with GL appearance, time to onset, and duration of action. Results: Responder rates were significantly higher for ASI vs placebo (88.3% vs 1.4%; P < 0.0001) at day 29 by ILA and all time points by ILA ( P < 0.0001-0.0441) and SSA ( P < 0.0001-0.0036). Sixty percent of patients reported onset of treatment response on or before day 3 ( P < 0.0001 vs placebo), and in 5% of patients, efficacy by ILA lasted 6 months (day 183; P = 0.0441 vs placebo). Patient satisfaction rates were significantly higher for ASI vs placebo at all visits ( P < 0.0001). Safety was comparable with the known abobotulinumtoxinA profile. Conclusions: ASI was significantly efficacious for improving moderate or severe GL vs placebo by investigator and patient assessment. ASI was associated with high patient satisfaction, a long duration of action, and comparable safety profile to abobotulinumtoxinA. Level of Evidence: 1: